Penetration of Piperacillin/Tazobactam Into Gynecologic Tissues Following a Single Loading Dose Prior to Hysterectomy - William F. O'Brien; Shelley George (Hindawi Limited, 1994)
Objective: This study was undertaken to determine plasma and pelvic tissue concentrations of piperacillin/tazobactam following a single intravenous administration.